Reference in the poetry of Ibn Hayyus - Al-mulqi, Ahmad Abed Al-kareem (Dirasat: Human and Social Sciences, 2025)
Objectives: This research addresses reference in the poetry of Ibn Hayyus Al-Dimashqi, aiming to demonstrate the function, types, and structure of referential tools, given their fundamental role in the coherence, cohesion, and highlighting the importance of reference in distinguishing a text in which it is used from other texts. Methods: The research follows the descriptive analytical approach, which focuses on tracing the phenomenon to uncover the extent to which reference mechanisms are achieved in Ibn Hayyus' poetry. This aids in analyzing and categorizing this phenomenon, understanding the poetic text, its implications, and elucidating its aesthetics in his poetry. Results: The research concludes that reference in Ibn Hayyus' poetry works to connect linguistic elements, contributing to its cohesion and coherence, playing a significant role in creating textual features through advanced or delayed connections. So much so that the poetic text almost interprets itself within the framework of a single text. Conclusion: The research concludes that Ibn Hayyus' poems are hardly devoid of reference to pronouns and nouns, revealing their secrets to make the text more comprehensive and rich in application.